Review of the genus Daidalotarsonemus De Leon (Acari: Prostigmata: Tarsonemidae) - Rezende, José Marcos [UNESP]; Bauchan, Gary; Lin, Jian-Zhen; Ochoa, Ronald; Lofego, Antonio Carlos [UNESP] (Magnolia Press, 2024)
We review the genus Daidalotarsonemus (Acari: Prostigmata: Tarsonemidae), including information about its taxonomy, phylogeny and distribution. In total, 42 species are listed, which the original descriptions register from 15 countries. Among them three new species are described and ten species are redescribed. Also, Mandarin descriptions for four species are translated to English, and one species is transferred to species inquirenda status. An identification key based on females is provided. Biological and biogeographical aspects of the genus are also briefly discussed. The cladistic analysis returned a single most parsimonious tree of 212 steps (CI 48, RI 76) and reinforces the hypothesis of monophyly for Daidalotarsonemus. According to it, the genus is primarily divided into two well-defined branches (A and B): the first based on two synapomorphies and the second by one synapomorphy and one homoplasy, all related to the dorsal setae d and e, respectively. The American continent hosts most of the known diversity for this group; however, the data indicates Daidalotarsonemus has a worldwide distribution, spread throughout a variety of biomes from savannahs to temperate forests.
Keywords: biodiversity; cladistics; phylogeny; taxonomy